Russian History Studies in Latin America and Spain (2001-2021) - Baña, Martín (2022)
Studies about Russian history in Latin America and Spain still are poorly developed. However, during the last three decades, books and articles about the Eurasian region began to appear in Spanish, in most of the cases incorporating documents in Russian language and including the latest publications in the international field. Although the interest about Russian history arose, in many cases, for political motivations –where the topic of the Russian Revolution was central–, researches soon turned towards other dimensions and chronologies, addressing cultural, economic and social issues not only about the 20th Century but also the 19th Century, and even a few centuries earlier. Research development is not uniform throughout the region and depends on institutional contexts, which are not always stable, and do not always have the necessary monetary funds. However, some production centers such as Argentina, Chile, Mexico and Spain stand out in the field. The spatial distance from Latin America to Russia can be a detriment in terms of access to documentation and bibliography. But, at the same time, it is an advantage for these countries to distance itself from the object of study and to propose other explanations that can complement or even discuss the dominant ones in order to make original contributions to the international field of studies about Russian history.